The Relationship Between Self-Acceptance and Treatment Compliance Levels of Pulmonary Tuberculosis Patients: The Relationship Between Self-Acceptance and Treatment Compliance Levels of Pulmonary Tuberculosis Patients - Sari, Gevi Melliya; Puspita, Enny; Bagus Sasmito, Nanang; Uswatun Sholikhah, Dwi (Jurnal Ilmu-Ilmu Kesehatan, 2025)
Pulmonary tuberculosis (TB) was an infectious disease caused by a rod-shaped bacterium (bacillus) known as Mycobacterium tuberculosis. It is transmitted through the saliva or phlegm of an infected person, which contains the pulmonary tuberculosis bacillus. Mycobacterium tuberculosis often attacks the lungs but can also affect the skin, lymph nodes, bones, and meninges. TB is both curable and preventable. The purpose of this study was to determine the relationship between self-acceptance and treatment adherence in patients with pulmonary tuberculosis. This study used a quantitative approach with a cross-sectional design. The population was all pulmonary tuberculosis patients within the Nguling Pasuruan Community Health Center (Puskesmas). A purposive sampling technique was used to select 30 respondents. The study instrument used the MMAS-8 self-acceptance questionnaire. Data analysis used the Spearman Rank test with a p-value ≤ 0.05. The Spearman Rank test results yielded a p-value of 0.000, meaning a p-value <0.05, indicating a strong relationship between self-acceptance and treatment adherence in pulmonary tuberculosis patients. Healthcare professionals are expected to assist patients by increasing their knowledge, providing psychological support, and fostering self-acceptance regarding their illness. It is hoped that with good self-acceptance, patients will be able to optimally comply with treatment.